Together we can stop the Diablo nuke
The Poster reads: 'Together we can stop the Diablo nuke. Rally in support of the occupation, music and speakers. Special Guests: Daniel Ellsberg, Barry Commoner, Port San Luis Beach. Sunday, August 7, Noon. Bring lunch, but please no alcohol, drugs or pets. Sponsored by PEOPLE GENERATING ENERGY IN CONJUNCTION with THE ABALONE ALLIANCE.'